Analisis Pemanfaatan Media Sosial Sebagai Strategi Promosi Dan Pemasaran Bisnis Rumahan “ Buket Novi Sari ” - Syofiah Harahap (Sekolah Tinggi Ilmu Ekonomi NU Trate Gresik, 2021)
Home business is one type of micro and small business (MSME) which is seen from its economic scale which is still low but is able to become one of the important parts in the economy of a country with the number of home businesses currently very large and dominant. The purpose of this study was to find out and analyze the use of social media as a promotion and marketing strategy by the